Bet hedging in desert winter annual plants: optimal germination strategies in a variable environment. (7th January 2014) - Gremer, Jennifer R.; Venable, D. Lawrence; Buckley, Yvonne
Abstract In bet hedging, organisms sacrifice short‐term success to reduce the long‐term variance in success. Delayed germination is the classic example of bet hedging, in which a fraction of seeds remain dormant as a hedge against the risk of complete reproductive failure. Here, we investigate the adaptive nature of delayed germination as a bet hedging strategy using long‐term demographic data on Sonoran Desert winter annual plants. Using stochastic population models, we estimate fitness as a function of delayed germination and identify evolutionarily stable strategies for 12 abundant species in the community. Results indicate that delayed germination meets the criteria as a bet hedging strategy for all species. Density‐dependent models, but not density‐independent ones, predicted optimal germination strategies that correspond remarkably well with observed patterns. By incorporating naturally occurring variation in seed and seedling dynamics, our results present a rigorous test of bet hedging theory within the relevant environmental context.